Study of extraction process and characterization of poly-3-hydroxyalkanoate produced from Alcaligenes latus - Shawaphun, Sarinya; Manangan, Thara (Asia-Pacific Journal of Science and Technology, 2017)
In order to obtain high extraction yield and proper quality of poly-3-hydroxyalkanoate (PHA) fromAlcaligeneslatus,eachof3extractionsteps;pretreatmentstep,extractionstepandpurificationstepwassystematically investigated. In pretreatment step, cell lytic pretreatment using various organic solvents and mechanical agitations were studied. Comparison of various extraction techniques and solvent extraction parameters including continuous extractionanddirect extraction was made. Thepurificationstep mainlyfocusedonrecrystallizationof the extracted polymerusingpropersolvents.Finally,mostextractedpolymersthenwereidentifiedbyFTIR andNMR spectroscopy andalsocharacterizedbydifferential scanningcalorimetry(DSC)anddilutesolutionviscometry(DSV) for thermal property and molecular weight, respectively.